Innovative Mode of Visual Communication Design Practice Teaching Based on Big Data - Wang, Xiaojun (Journal of physics. Conference series, 2021)
With the advent of the era of big data, big data has affected all walks of life, and to a certain extent some questions have been raised about the logical way of teaching visual communication design courses. Therefore, there are serious problems in the teaching of visual communication design courses. This article introduces some innovations and practices in practical teaching of creative visual communication design courses, and uses these methods to conduct a series of research and discussion on creative visual communication design courses. Universities in our country must reform their teaching and training methods and cultivate talents who can meet the needs of the development society in the era of big data. Especially some undergraduate colleges that have just entered the undergraduate stage should teach in the course of visual communication design innovation. This path has undergone positive changes. In order to cultivate students’ cultural, creative awareness and technology, visual communication design has a close relationship with the development of creative industries. In the education process, the integration of technology and aesthetics should be emphasized. In the era of mobile media, artistic creation results should be combined with H5, video, illustration, and virtual. Due to the comprehensive effect of reality and other factors, talent training not only possesses the cultural heritage, design power and new technology required by the creative industry. Therefore, innovation and practice of education and teaching for this course are imperative. At present, our country is establishing a dynamic scientific visual communication curriculum education and research system focusing on the development of visual communication symbols and language research. Visual communication design refers to the design of using visual symbol language to convey information. In China, the change of modern design concepts is a new vocabulary that has gradually been accepted by people in the past 10 years and has become an important part of the integration of university design education and traditional design fields. The content and direction can include all educational courses with visual information as the main content. The professional direction is gradually recognized and used in domestic design schools. Experimental research results show that in the current era of big data, the innovative trend of practical teaching of visual communication design is inevitable, and there is an urgent need to reform and innovate teaching methods.